2003
DOI: 10.1002/glia.10271
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the osmosensitive taurine release and cell volume regulation by cytosolic Ca2+ rise in cultured cerebellar astrocytes

Abstract: Hyposmolarity (-30%) in cultured cerebellar astrocytes raised cytosolic Ca2+ concentration ([Ca2+]i) from 160 to 400 nM and activated the osmosensitive taurine release (OTR) pathway. Although OTR is essentially [Ca2+]i-independent, further increase in [Ca2+]i by ionomycin strongly enhanced OTR, with a more robust effect at low and mild osmolarity reductions. Ionomycin did not affect isosmotic taurine efflux. OTR was decreased by tyrphostin A25 and increased by ortho-vanadate, suggesting a modulation by tyrosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
32
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 46 publications
6
32
2
Order By: Relevance
“…Similar to our findings, Cardin et al have demonstrated that the Ca 2ϩ ionophore ionomycin enhances volume-sensitive taurine release in cerebellar astrocyte cultures through a CaMKII-dependent mechanism (27). In the same study, CaMKII inhibition was ineffective in blocking control swelling-induced release in the absence of ionomycin (27). Using a phospho-Thr286 antibody recognizing the autophosphorylated active form of CaMKII (55), we confirmed that H 2 O 2 stimulates CaMKII activity in swollen astrocytes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to our findings, Cardin et al have demonstrated that the Ca 2ϩ ionophore ionomycin enhances volume-sensitive taurine release in cerebellar astrocyte cultures through a CaMKII-dependent mechanism (27). In the same study, CaMKII inhibition was ineffective in blocking control swelling-induced release in the absence of ionomycin (27). Using a phospho-Thr286 antibody recognizing the autophosphorylated active form of CaMKII (55), we confirmed that H 2 O 2 stimulates CaMKII activity in swollen astrocytes.…”
Section: Discussionsupporting
confidence: 91%
“…These data suggest that CaMKII is a critical component of the H 2 O 2 -dependent potentiation of swelling-sensitive EAA release. Similar to our findings, Cardin et al have demonstrated that the Ca 2ϩ ionophore ionomycin enhances volume-sensitive taurine release in cerebellar astrocyte cultures through a CaMKII-dependent mechanism (27). In the same study, CaMKII inhibition was ineffective in blocking control swelling-induced release in the absence of ionomycin (27).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…VB). Addition of Ca 2ϩ -mobilizing agonists does not elicit taurine release under isotonic conditions but potentiates the swelling-induced taurine efflux from a variety of cells presumably via pathways involving CaM and CaMKII, PI3K, and PKC (112,222,451,551,661). In contrast, a concentration (3 nM) of LTD 4 too low to elicit detectable Ca 2ϩ mobilization induces taurine release under isotonic conditions (see Fig.…”
Section: Mechanisms Of Activation Of the Taurine Efflux Pathwaymentioning
confidence: 91%